Willingness to pay of the households for solar energy-a case study in Kuala Lumpur Malaysia [Public acceptance and willingness to pay for solar energy- a case study in Kuala Lumpur, Malaysia] - Rafia, Afroz; Morshed, Niaz; ., Md Muhibbullah; Duasa, Jarita; Haniza, Khalid (USIM Tijarah Holdings Sdn. Bhd., 2019)
The objective of this study is to analyze and evaluate public acceptance and their willingness to pay (WTP) for solar energy for their household use in Kuala Lumpur. For this reason, a contingent valuation method (CVM) was conducted to recognize the WTP of individuals and the features persuading it. Inhabitants of 400 families in Kuala Lumpur were questioned face to face. A logit model was estimated to investigate the factors that may affect the willingness of the households to pay additional electricity bills for solar energy. It was found that the average WTP value per family is RM 16, which will be paid monthly as an additional charge in electricity bills. The results of the logit model show that income, household size and knowledge about climate change positively and significantly affect the WTP of the households to pay additional electricity bills.